The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2174/1573399810666140825154815
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Current and Upcoming Strategies Implied for the Therapy of Type 2 Diabetes Mellitus

Abstract: Population explosion, urbanization, changes in lifestyle management, improper food habits and various other factors play focal contributors in the massive prevalence of type 2 diabetes mellitus in the developing countries. Although insulin is the cornerstone in the management of type 1 diabetes; insulin, anti-hyperglycemic and hypoglycemic agents are proved to be effective in type 2 diabetes, although their efficacy decreases with the progress of the disease. Moreover a significant number of side effects, most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Despite lifestyle and pharmacological interventions, patients with type 2 diabetes mellitus continue to experience increases in glucose levels over time, which is likely to be as a consequence of declining β-cell function. One study found that approximately two-thirds of patients with type 2 diabetes mellitus in developed countries do not effectively control their glucose levels and that an even greater proportion does not do so in developing countries, particularly in China ( 2 ). A major reason for this failure is the progressive nature of type 2 diabetes mellitus, which makes it difficult for patients to maintain target levels of glycated hemoglobin (hemoglobin A1c; HbA1c) using traditional glucose-lowering agents, and usually requires them to take multiple antihyperglycemic agents (AHAs) to attain or maintain glycemic control.…”
Section: Introductionmentioning
confidence: 99%
“…Despite lifestyle and pharmacological interventions, patients with type 2 diabetes mellitus continue to experience increases in glucose levels over time, which is likely to be as a consequence of declining β-cell function. One study found that approximately two-thirds of patients with type 2 diabetes mellitus in developed countries do not effectively control their glucose levels and that an even greater proportion does not do so in developing countries, particularly in China ( 2 ). A major reason for this failure is the progressive nature of type 2 diabetes mellitus, which makes it difficult for patients to maintain target levels of glycated hemoglobin (hemoglobin A1c; HbA1c) using traditional glucose-lowering agents, and usually requires them to take multiple antihyperglycemic agents (AHAs) to attain or maintain glycemic control.…”
Section: Introductionmentioning
confidence: 99%
“…GLP-1 and PYY) play an important role in the regulation of glucose homeostasis [5,7,20,21]. Elucidating the mechanisms responsible for improvement in plasma glucose concentration after bariatric/metabolic surgery will help identify potential targets for diabetes therapy [14].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, improving β‐cell function in people with type 2 diabetes improves glucose control; thus, therapies that improve β‐cell function (e.g. GLP‐1 receptor agonists and thiazolidinediones) produce durable reductions in HbA 1c in type 2 diabetes . Several studies have demonstrated marked improvement in β‐cell function in type 2 diabetes following gastric bypass , but no study has assessed the impact of ileal transposition and transit bipartition on β‐cell function in people with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…3 A Study showed that control of T2DM is not up to the mark in the developed countries in about 2/3 rd of patients and this fact is even more pronounced in the developing countries. 4 In Pakistan, the prevalence T2DM is quite high and approximately 6.3 million people have this disease. This is likely to increase and by 2030 about 11.4 million peoples will have diabetes if appropriate measures are not taken.…”
Section: Introductionmentioning
confidence: 99%